(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This study delves into the nuanced interconnection between pedagogy and administration within educational contexts. Pedagogy encompasses the methodologies and strategies employed in teaching and learning processes, while administration entails the governance and supervision of educational establishments. The research investigates the intersection and mutual influence of these domains, elucidating their combined impact on the efficacy of educational systems. Drawing upon extant literature and empirical data, the study scrutinizes diverse facets of the correlation between pedagogy and administration, providing valuable insights into their synergistic contributions to shaping educational outcomes.